Effects of the mechanical vibrations on the thrust force characteristics for the PMLM driven motion system. (1st August 2022) - Yang, Xiaojun; Song, Bifeng; Xuan, Jianlin
Highlights: The effects of the mechanical vibration on the magnetic field distribution are calculated. The effects of the mechanical vibration on the drive current are represented. The coupling between the mechanical vibrations and servo system is analyzed. The effects of the mechanical vibration on the direct drive motion system are discussed. Abstract: In the permanent magnet linear motor (PMLM) driven system, the unique zero-transmission structure intensifies the coupling between servo system and mechanical system. This paper presents the effects of the mechanical vibrations on the characteristics of the thrust force for the PMLM driven motion system. Firstly, the mechanical dynamic model of the direct drive system is established using Lagrange equation, and the main mechanical vibration forms are analyzed. Then, the influences of different mechanical vibrations on the distribution of air–gap magnetic field and the drive current are studied. Finally, the thrust spectrum characteristics of PMLM considering the mechanical vibrations are analyzed and verified by experiments. The results show that the mechanical vibrations will directly affect the amplitudes of the nominal thrust and the original thrust harmonics of PMLM. In addition, it will be coupled with the magnetic field harmonics and the drive circuit harmonics, which generates a large number of new thrust harmonics and worsen the thrust fluctuation and dynamic precision of the motion system.